2011
DOI: 10.1021/ja204891v
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemical Investigation of Intramolecular and Interfacial Electron-Transfer Rates Reveals Differences Between Nitrite Reductase at Rest and During Turnover

Abstract: A combined fluorescence and electrochemical method is described that is used to simultaneously monitor the type-1 copper oxidation state and the nitrite turnover rate of a nitrite reductase (NiR) from Alcaligenes faecalis S-6. The catalytic activity of NiR is measured electrochemically by exploiting a direct electron transfer to fluorescently labeled enzyme molecules immobilized on modified gold electrodes, whereas the redox state of the type-1 copper site is determined from fluorescence intensity changes caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 52 publications
5
44
0
Order By: Relevance
“…Several pulse radiolysis162122, protein-film voltammetry919 and laser-flash-photolysis studies57 of different CuNiRs have shown that during single turnover experiments, the rate of inter-Cu ET is decreased by the presence of nitrite. The degree of inhibition is pH-dependent and for wild-type Ax NiR at pH 7 the k obs decreases from 370 to ~250 s −1 at saturating nitrite concentrations57.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several pulse radiolysis162122, protein-film voltammetry919 and laser-flash-photolysis studies57 of different CuNiRs have shown that during single turnover experiments, the rate of inter-Cu ET is decreased by the presence of nitrite. The degree of inhibition is pH-dependent and for wild-type Ax NiR at pH 7 the k obs decreases from 370 to ~250 s −1 at saturating nitrite concentrations57.…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been shown that protons, in addition to being a substrate in this reaction, are involved in controlling the rate of electron transfer (ET) between the type-1 Cu (T1Cu) centre and the catalytic type-2 Cu (T2Cu) centre of the enzyme56789.…”
mentioning
confidence: 99%
“…Extensive spectroscopic and structural studies of CuNiRs (Strange et al, 1999;Boulanger et al, 2000;Boulanger & Murphy, 2001;Tocheva et al, 2004Tocheva et al, , 2007Antonyuk et al, 2005;Krzemiń ski et al, 2011;Wijma et al, 2006;Hough et al, 2008;Leferink et al, 2011Leferink et al, , 2012 have suggested a general catalytic mechanism in which bound water in the resting state is replaced by nitrite, and internal electron transfer occurs between the T1Cu and T2Cu sites. Two protons are required for the reaction, which are thought to be provided by Asp98 (Asp CAT ) and His255 (His CAT ) via a bridging water molecule, leading to cleavage of the bound NO 2 À to produce NO and H 2 O. Conformational rearrangements of Asp CAT have been proposed to be important in substrate guidance and proton transfer (Antonyuk et al, 2005), while His CAT may respond to the redox state.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, at high pH or high nitrite concentrations, the binding of nitrite to oxidized T2Cu occurs prior to ET. [24,39,40] Additionally,t he reactionm echanisms of CuNiRs have been discussed as ar esult of many theoretical studies. [24,39,40] Additionally,t he reactionm echanisms of CuNiRs have been discussed as ar esult of many theoretical studies.…”
Section: Introductionmentioning
confidence: 99%